Little treasures - Price, Katie; Design, Dyanamo (London A Bantam book, 2007)
Jess, Mel, Amber, Sam and Cara are lucky enough to be able to spend as much time as they can with their favourite ponies at Vicki's Riding School. Grooming, sweeping the yard, even mucking out is fun when you love ponies as much as they do. As long as you can ride a pony and follow clues you'll be fine ...With the girls and their ponies all performing so well at the Riding School, Vicki decides to challenge them to something different - a charity Treasure Hunt! All the girls are excited and hoping to win. But snooty livery girl Henrietta is also desperate to come first and when the girls find some surprise treasure during the hunt, it looks like she might just do that ..